FERMENTATION OF COCOA (Theobroma cacao L.) POD HUSK AND ITS HYDROLYSATE FOR ETHANOL PRODUCTION USING IMPROVED STARTER CULTURES (2012)
Fossil fuel, a main but dwindling energy source for automobiles, causes emission of environment unfriendly oxides of carbon. These contribute substantially to greenhouse gases which bring about climate change. There is therefore the need for sustainable source of energy like ethanol an environmental friendly bioenergy. Hence this study was aimed at the fermentation of cocoa pod husk for ethanol production. Isolates of yeast were obtained from sun-dried Cocoa Pod Husk (CPH), subjected to spontaneous submerged fermentation for 7 days. Five strains of Saccharomyces sp. (MX1, MX2, MX3, MX4 and MX5) with high frequency of occurrence were selected for further studies. The MX1 and MX2 were used for genetic modifications. Dried CPH was subjected to chemical analysis and pretreatment using particle size reduction and high pressure liquid hot water at 130oC for 30 minutes. Acid and enzymatic hydrolysis of the pretreated CPH was carried out using standard method. Products of the hydrolysis were analysed with high performance liquid chromatography. Two genes XL1 (xylose reductase) and XL2 (xylitol dehydrogenase) encoding pentose utilization were obtained from genomic DNA of Pichia stipitis (CBS 6054) using basic local alignment search tool. Primers of these genes were designed with Saccharomyces genome database, amplified with Polymerase Chain Reaction (PCR) and purified. The amplicon (genes) were ligated into plasmid vectors (pGAPZA and pVT100-U). Strains MX1 and MX2 were transformed with these construct using lithium acetate method. Physiological characterization of the selected unmodified yeast strains and the two genetically-modified strains was done under different environmental conditions including temperatures, pH and varied concentrations of acetic acid. The CPH hydrolysates were fermented for 120 hours using the unmodified and genetically-modified yeast strains respectively and the ethanol yield determined. Data were analysed using ANOVA. Twenty yeast isolates identified as Saccharomyces cerevisiae (80%) and Saccharomyces uvarum (20%) were obtained. Chemical composition of CPH included hemicellulose (13.9%) cellulose (18.6%) and lignin content (14.2%). Acid hydrolysis yielded 50.1% glucose, 11.97% xylose, 11.2% mannose while enzymatic hydrolysis gave 31.7% glucose, 4.8% mannose and 16.8% galactose. The inserted gene XL1 had 318 amino acids polypeptides while XL2 had 363 amino acid polypeptides. Restriction enzyme analysis and colony PCR confirmed the transformational integration of these constructs into Saccharomyces cerevisiae MX1 and MX2. The five isolates had optimal growth at 30 – 40oC and pH of 4.0 – 5.5. However the genetically-modified yeast strains were able to utilize xylose and arabinose carbon sources better than the unmodified types and also tolerated low concentration of acetic acid than the unmodified types. Ethanol production was highly significant (p0.05) in the modified starters (29.7g/L) than the unmodified strains (14.0g/L). Genetically-modified organisms performed better in ethanol production than the non-modified organisms. The application of genetic modification of microorganisms will aid the potential use of waste biomass like cocoa pod husk for bioenergy production and this will contribute significantly to reducing greenhouse gases associated with climate change.